Digital Marketing Strategy for Gen-Z: A Mathematical Modelling Approach on the Impact of Influencer Marketing and Customer Experience on Skincare Purchase Decision - Pesta Gultom; Tri Wulandari; Tan Kim Hek (TALENTA Publisher, Universitas Sumatera Utara, 2026)
Generation Z is a digital consumer group that has a significant influence on market direction, especially in the beauty and skincare industry. Their characteristics of being closely connected to social media, responsive to trends, and having a preference for social values and personalization, demand more adaptive marketing strategies. Influencer marketing and customer experience are two strategies frequently used to reach this group. However, the relative effectiveness of each strategy remains an open question, especially in a local context such as Medan City. Therefore, this study is important to provide a data-based understanding of the influence of these two factors on skincare purchasing decisions, while identifying the most dominant variables. This study aims to: (1) analyze the influence of influencer marketing on skincare purchasing decisions among Generation Z in Medan City; (2) analyze the influence of customer experience on purchasing decisions; and (3) examine the dominant factors that influence these decisions. The method used is a quantitative approach with a purposive sampling technique, through the distribution of closed questionnaires. The collected data will be analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS software because the variables studied are latent variables. The research results can be concluded that: (a) Influencer marketing has been shown to have a significant influence on skincare purchases among Gen-Z, and (b) Customer experience also has a significant influence on purchasing decisions.